Журналістська дисципліна в політичній культурі - Виходець, О. М.; Выходец, О. М.; Vyhodec, О. (My University, 2010)
It was became the attempt to attract attention to journalist discipline which is not the selfpurpose. This is the way achieve purpose until publication information.
Виходець О. М. Журналістська дисципліна в політичній культурі / О. М. Виходець // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 325-330.
Keywords: журналістика; політична культура; журналістська дисципліна; публікація інформаційно-публіцистичних досліджень; журналистика; политическая культура; журналистская дисциплина; публикация информационно-публицистических исследований; journalism; political Culture; journalistic discipline; the publication of information and journalistic research